The Impact of KUR Disbursement on MSME's Credit Growth - Ridha, Muhammad Hafizh; Ashari, Hasan; Damhuri, Taufik (Puslatbang KDOD Lembaga Administrasi Negara, 2024)
MSMEs support social and economic growth through employment and poverty reduction. Recently, MSMEs have had some challenges, including limited access to capital. Hence, the government should participate in solving those challenges, such as creating various MSME financing empowerment programs with multiple schemes, such as interest subsidies, guarantees, or risk sharing. KUR become an alternative instrument to support MSME financing in Indonesia, with substantial implications for economic growth. This study aims to provide empirical evidence regarding the effect of KUR Disbursement on MSME's Credit Growth with MSME's Commercial Credit Growth as a mediating variable. The data covered 33 provinces in Indonesia from 2015-2021. Using the Random Effect Model and Ordinary Least Square (OLS) Regression, the results indicated that (1) KUR Disbursement does not affect MSME's Credit Growth, (2) KUR Disbursement negatively influences MSME's Commercial Credit Growth, (3) MSME's Commercial Credit Growth positively influences MSME's Credit Growth, and (4) MSME's Commercial Credit Growth does not mediate the relationship between KUR Disbursement on MSME's Credit Growth means MSME's Commercial Credit Growth cannot act as a mediating factor in enhancing the effect of KUR Disbursement on MSME's Credit Growth